Perancangan Sistem Aplikasi Absensi Real Time untuk Meningkatkan Efisiensi Manajemen Kehadiran PT. Asia Sinergi Solusindo - Wahyu Hidayat; Fajar Alim Ba’a; Oki Prasetio; Wasis Haryono (Switch : Jurnal Sains dan Teknologi Informasi, 2025)
The advancement of information technology has driven the need for more effective and efficient attendance systems, especially for companies with a distributed workforce. PT. Asia Sinergi Solusindo faces challenges in managing employee attendance in real-time based on predefined work locations. This study aims to design a location-based attendance application system utilizing Global Positioning System (GPS) technology to ensure employees can only mark attendance at locations specified by the administrator. The system was developed using the *waterfall* software development methodology, encompassing requirements analysis, system design, implementation, and testing. The application was built on the Android platform with cloud-based database integration to centrally store attendance data. The results show that the system enhances attendance data accuracy, reduces fraud risks, and facilitates real-time employee attendance monitoring. Thus, this application is expected to provide an effective solution to support attendance management at PT. Asia Sinergi Solusindo.